2021
DOI: 10.3389/fpls.2021.727302
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes and MicroRNAs Affecting Pre-harvest Sprouting in Rice (Oryza sativa L.) by Transcriptome and Small RNAome Analyses

Abstract: Pre-harvest sprouting (PHS) is one of the primary problems associated with seed dormancy in rice (Oryza sativa L.). It causes yield loss and reduces grain quality under unpredictable humid conditions at the ripening stage, thus affecting the economic value of the rice crop. To resolve this issue, understanding the molecular mechanism underlying seed dormancy in rice is important. Recent studies have shown that seed dormancy is affected by a large number of genes associated with plant hormone regulation. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…Given DEF8 is expressed at high level in rice grains and adjoint tissues ( Figure 1C ), and the expression keeps rising during grain irrigation and ripening ( Supplemental Figure S1 ), we suspect that DEF8 might function in regulating seed dormancy and pre-harvest sprouting (PHS), a global issue with serious impact on crop quality and yield ( Park et al, 2021 ; Sohn et al, 2021 ), for the following reasons: (1) abscisic acid (ABA) maintains seed dormancy and inhibits seed germination, while gibberellin (GA) breaks dormancy and promotes seed germination ( Hartmann et al, 2011 ; Miao et al, 2018 ; Tuan et al, 2018 , 2019 ). DEF8 expression was strongly induced by ABA ( Supplemental Figure S6 ), consistent with a proposed function of maintaining dormancy.…”
Section: Discussionmentioning
confidence: 99%
“…Given DEF8 is expressed at high level in rice grains and adjoint tissues ( Figure 1C ), and the expression keeps rising during grain irrigation and ripening ( Supplemental Figure S1 ), we suspect that DEF8 might function in regulating seed dormancy and pre-harvest sprouting (PHS), a global issue with serious impact on crop quality and yield ( Park et al, 2021 ; Sohn et al, 2021 ), for the following reasons: (1) abscisic acid (ABA) maintains seed dormancy and inhibits seed germination, while gibberellin (GA) breaks dormancy and promotes seed germination ( Hartmann et al, 2011 ; Miao et al, 2018 ; Tuan et al, 2018 , 2019 ). DEF8 expression was strongly induced by ABA ( Supplemental Figure S6 ), consistent with a proposed function of maintaining dormancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that microRNAs (miRNAs) are dependent on hormonal regulation in plants [ 118 ]. Recently, Park et al [ 117 ] identified two candidate miRNAs (osa-miR5827 and osa-miR1862h) associated with two pre-harvest sprouting-related genes OsFbox594 and OsbHLH084 , respectively. In addition to transcription factors, NCED ( OsNCEDs ) and CYP ( OsCYP707As ) genes were differentially expressed by comparing the transcriptome profiles of Korean cultivars [ 119 ].…”
Section: Omics Approaches For Pre-harvest Sprouting In Ricementioning
confidence: 99%
“…LTG qLTG-3, qLTG-4, qLTG-5-1, qLTG-5-2, qLTG- Transcriptomics studies are considered an effective method for comparative transcriptome profiling, providing insight into the mechanism of gene regulation and networks controlling various complex biological processes, especially signal transduction [86]. Highthroughput methods have been used to accurately characterize and quantify the complete set of RNAs in a given organ such as panicle, embryo and endosperm, tissues, or cells in different rice materials [114][115][116][117]. To determine the genes involved in pre-harvest sprouting and the corresponding biological processes such as seed dormancy, germination, and maturation, RNA and small-RNA sequencing were performed with different genotypes (Table 2).…”
Section: Omics Approaches For Pre-harvest Sprouting In Ricementioning
confidence: 99%
“…PHS is the precocious germination of grains before harvest. The premature germination of grains within panicles in paddy fields occurs when crops are exposed to humid weather conditions, favorable for germination, during the grain ripening stages ( Hanumanthappa et al., 2016 ; Park et al., 2021 ). Therefore, PHS is a serious global agricultural issue in terms of both production and economics and requires urgent preventive measures ( Tai et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%